Systematic Literature Review (SLR) : Peran Game Edukasi dalam Meningkatkan Motivasi Belajar Matematika Siswa Sekolah Dasar - Putri Wahyuni; Adelia Syarifuddin; Mutmainnah; Hamda Hamda; Sahrul Syawal (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the role of educational games in enhancing elementary school students’ motivation to learn mathematics through a Systematic Literature Review (SLR) approach. Data were collected from scientific articles obtained via Google Scholar with the assistance of Publish or Perish. The selection process was conducted using the PRISMA framework, resulting in 10 articles that met the inclusion criteria. The results of the study indicate that the use of educational games, such as Wordwall, Kahoot, and Math Playground, has proven effective in enhancing students’ motivation to learn mathematics through interactive, engaging, and enjoyable learning experiences. Additionally, educational games also contribute to improving student engagement, conceptual understanding, and critical thinking skills.